2017
DOI: 10.1121/1.4987243
|View full text |Cite
|
Sign up to set email alerts
|

Apparent sound insulation in cross-laminated timber buildings

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. NRC Publications Record / Notice d'Archives des publications de CNRC:http://nparc.cisti-icist.nrc-cnrc.gc.ca/eng/view/object/?id=27e0a78f-5739-4b23-90e1-442155ff4d25 http://nparc.cisti-icist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The FE segment used in the WFE model had dimensions of 10 mm × 10 mm and consisted of a stack of 6 cubic SOLID185 ANSYS elements. The properties of the orthotropic solid used to model each layer are given in Table 1 and are identical to the estimates used in Yang et al 7 which were taken from Hoeller et al 22 Note that the coordinate system utilised for the material properties listed in this table differs from that used previously. Here, the x -axis is aligned with the length of the beams in each panel whilst the z -axis runs through the panel thickness.…”
Section: Sound Transmission Loss Of Double-leaf Clt Wall Systemsmentioning
confidence: 99%
“…The FE segment used in the WFE model had dimensions of 10 mm × 10 mm and consisted of a stack of 6 cubic SOLID185 ANSYS elements. The properties of the orthotropic solid used to model each layer are given in Table 1 and are identical to the estimates used in Yang et al 7 which were taken from Hoeller et al 22 Note that the coordinate system utilised for the material properties listed in this table differs from that used previously. Here, the x -axis is aligned with the length of the beams in each panel whilst the z -axis runs through the panel thickness.…”
Section: Sound Transmission Loss Of Double-leaf Clt Wall Systemsmentioning
confidence: 99%
“…These studies revealed, on the one hand, the complexity in defining acoustic calculation models and, on the other, the problems connected with the effective achievement of the expected sound insulation. Several parallel lines of research have therefore developed: Laboratory and on-site characterization of the properties of sound insulation and impact noise level of CLT elements with the creation of the first repertoires for the use of acoustic performance data in calculation models by Hoeller et al [55], Homb et al [56], Schoenewadl et al [57], and Zeitler et al [58]; the study of the vibro-acoustic behavior of CLT panels and their radiation efficiency by Santoni et al [59,60] with the effects on the modelling of the acoustic behavior of the panels developed by Morandi et al [61] and validated through comparisons between laboratory measurements and models; the study on the influence of the joints between CLT panels on the on-site acoustic performance by Guigou-Carter et al [62] and Morandi et al [63], which led to the inclusion of specific relationships for CLT in the standardized prediction methods. Di Bella et al [64,65] proposed parametric reference curves of acoustic insulation and the impact noise level for bare CLT structures in order to use the data available from laboratory measurements of the performance improvement provided by acoustic linings, in the absence of laboratory-measured data on complete structures.…”
Section: Overview On Basic Research On Clt Systemsmentioning
confidence: 99%
“…Although extensive laboratory tests have been carried out for the evaluation of the sound reduction and impact noise level index on several types of CLT building elements [55][56][57][58][126][127][128][129], the database available for the standardized prediction models is not sufficiently large if compared to other construction systems, both light and heavy.…”
Section: Airborne and Impact Insulation Properties Of Bare And Lined Clt Building Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wooden elements are mostly used for frames of small buildings (such as single-family houses and cabins), frames of non-load-bearing facades and for cladding (Treindustrien.no). The use of wood in large buildings also requires additional safety and attention with respect to fire safety and noise propagation; this is likely to introduce additional cost to the building process in order to satisfy the current building requirements (Structural Timber Association 2014, Buchanan et al 2014, Hoeller et at. 2017, Pagnoncelli and Morales 2016.…”
Section: Wooden Nearly Zero Energy Buildings (Nzebs) In Norwaymentioning
confidence: 99%